Diversity and flower-visiting frequency of insect pollinators associated with mustard blooms (Brassica campestris) in Kullu Valley, Himachal Pradesh - Kishor Kumar; Rajendra Singh Fartyal; K.S. Kanwal; Shipra Khanduri; Pragya Topal (Environment Conservation Journal)
Present study was conducted in Mohal Khad, Kullu Valley, Himachal Pradesh, investigated the diversity and flower-visiting frequency of insect pollinators on mustard (Brassica campestris). The visual sampling method during the peak bloom of mustards recorded a total of 24 species of insect pollinators from 4 orders, 13 families, and 19 genera, with Hymenoptera being the dominant order, while Coleoptera had the least presence. The Indian honeybee (Apis cerana indica) was the most frequently observed visitor, highlighting its significant role in pollination. Mustards act as an essential foraging source for insect pollinators during early spring in temperate regions, where they bloom earlier than other temperate crops.  The findings help emphasize the importance of mustard cultivation along with the conservation of native species, Apis cerana indica, over exotic ones for sustainable agriculture in the Himalayan region.